Low‐dose rituximab induction therapy is effective in immunological high‐risk renal transplantation without increasing cytomegalovirus infection. (3rd October 2020) - Yoshinaga, Kasumi; Araki, Motoo; Wada, Koichiro; Maruyama, Yuki; Mitsui, Yosuke; Sadahira, Takuya; Kubota, Risa; Nishimura, Shingo; Kobayashi, Yasuyuki; Takeuchi, Hidemi; Tanabe, Katsuyuki; Kitagawa, Masashi; et al.
Abstract : Objectives: To analyze the effect and impact of low‐dose rituximab induction therapy on cytomegalovirus infection in living‐donor renal transplantation. Methods: A total of 92 recipients undergoing living‐donor renal transplantation at Okayama University Hospital from May 2009 to August 2018 were evaluated retrospectively. Indications for preoperative rituximab (200 mg/body) were the following: (i) ABO major mismatch; (ii) ABO minor mismatch; (iii) donor‐specific anti‐human leukocyte antigen antibody‐positive; and (iv) focal segmental glomerulosclerosis. We excluded four recipients who were followed <3 months, five who received >200 mg/body rituximab and seven who received prophylactic therapy for cytomegalovirus. Results: There were 59 patients in the rituximab group and 17 in the non‐rituximab group. Groups differed significantly in age (median age 53 vs 37 years, respectively; P = 0.04), but not in sex (male 64% vs 65%, P = 1.00), focal segmental glomerulosclerosis (3% vs 0%, P = 1.00) or percentage of cytomegalovirus‐seronegative recipients of renal allografts from cytomegalovirus‐seropositive donors (12% vs 18%, P = 0.68). The estimated glomerular filtration rate did not differ significantly between groups until 24 months after transplantation. Cytomegalovirus clinical symptoms (10% vs 24%, P = 0.22), including fever ≥38°C (5% vs 12%, P = 0.31) and gastrointestinal symptoms (5% vs 12%, P = 0.31), and the 5‐year survival rates of death‐censored graft loss (90% vs 83%, P = 0.43) did not differ significantly between groups. Conclusions: Low‐dose rituximab induction therapy is effective in immunological high‐risk recipients without increasing cytomegalovirus infection in the absence of valganciclovir prophylaxis.